PENGADAAN TANAH UNTUK KEPENTINGAN UMUM DI TANAH KASULTANAN (STUDI KASUS PEMBANGUNAN JALAN TOL YOGYAKARTA-BAWEN) - Endriana, Eka Putri (PERSPEKTIF : Kajian Masalah Hukum dan Pembangunan, 2024)
The high rate of toll road construction aims to smooth traffic in developed areas and enhance the equitable distribution of development outcomes. One of the toll road constructions targeted to be operational in 2024 is the Yogyakarta-Bawen toll road. The construction of this toll road is considered important because Yogyakarta plays a role as a hub for economic development in southern Java. The issue that becomes important when constructing a toll road is the mechanism for acquiring land owned by residents to be converted into a road. This raises issues regarding the mechanism for land acquisition for public purposes on Sultanate land, which has distinct characteristics compared to privately owned land. In this study, a comparison will be made regarding the regulation of land acquisition for public interest in Law No. 2 of 2012 as amended by Law No. 6 of 2023 with the Regional Regulation No. 1 of 2017. Additionally, the study will examine how the mechanism of land acquisition for public interest on Sultanate land in the construction of the Yogyakarta-Bawen toll road. This research employs an empirical juridical research type with a statutory approach, a conceptual approach, and a case approach. The research results indicate that there are differences in the provisions regarding land acquisition for public purposes in Law No. 2 of 2012 compared to DIY Regional Regulation No. 1 of 2017.